Determination of wild animal sources of fecal indicator bacteria by microbial source tracking (MST) influences regulatory decisions. (1st November 2018) - Nguyen, K.H.; Senay, C.; Young, S.; Nayak, B.; Lobos, A.; Conrad, J.; Harwood, V.J.
Abstract: Fecal indicator bacteria (FIB) are used to assess fecal pollution levels in surface water and are among the criteria used by regulatory agencies to determine water body impairment status. While FIB provide no information about pollution source, microbial source tracking (MST) does, which contributes to more direct and cost effective remediation efforts. We studied a watershed in Florida managed for wildlife conservation that historically exceeded the state regulatory guideline for fecal coliforms. We measured fecal coliforms, enterococci, a marker gene for avian feces (GFD), and a marker gene for human-associated Bacteroides (HF183) in sediment, vegetation, and water samples collected monthly from six sites over two years to: 1) assess the influence of site, temporal factors, and habitat (sediment, vegetation, and water) on FIB and MST marker concentrations, 2) test for correlations among FIB and MST markers, and 3) determine if avian feces and/or human sewage contributed to FIB levels. Sediment and vegetation had significantly higher concentrations of FIB and GFD compared to water and thus may serve as microbial reservoirs, providing unreliable indications of recent contamination. HF183 concentrations were greatest in water samples but were generally near the assay limit of detection. HF183-positive results were attributed to white-tailed deer ( Odocoileus virginianus ) feces, which provided a false indication of human sewage in this water body. FIB and GFD were positively correlated while FIB and HF183 were negatively correlated. We demonstrated that birds, not sewage, were the main source of FIB, thus avoiding implementation of a total maximum daily load program (TMDL). Our results demonstrate that the concomitant use of FIB and MST can improve decision-making and provide direction when water bodies are impaired, and provides a strategy for natural source exclusion in water bodies impacted by wild animal feces. Graphical abstract: Image 1 Highlights: High FIB led to suspicion of sewage contamination in a stream managed for wildlife. Predictive modeling identified major factors influencing FIB levels e.g. seasons. Bird marker gene (GFD) levels were high throughout the year. Sewage markers (HF183) were attributed to cross reaction with deer feces. Natural bird sources contributed to FIB contamination in the water body.